y = -3x - 2
Therefore the slope is -3 and b is -2
2006-11-15 12:15:46
·
answer #1
·
answered by Megan M 2
·
0⤊
0⤋
Solve the equation for y; then the slope will be the coefficient of x. And b, or the y-intercept, will be the constant on the x side of the equation.
3x+y= -2
y= -3x-2 (Divided both sides by x).
In this case, the slop is -3 (or -3/1) and the y intercept is -2.
2006-11-15 20:18:55
·
answer #2
·
answered by SomeGuy 6
·
0⤊
0⤋
For this equation, you have to put it into the general form of y = mx + b.
You have the equation: 3x + y = -2
rearranging gives:
y = -3x - 2
comparing with the general formula: y = mx + b
we can deduce that:
m = -3 and b = -2.
So, the gradient (slope) is -3 and the y-intercept is -2.
2006-11-15 20:17:05
·
answer #3
·
answered by thugster17 2
·
0⤊
0⤋
the slope is -3 and b = -2
2006-11-15 20:20:52
·
answer #4
·
answered by superstar 2
·
0⤊
0⤋
x=-3 & y=6
2006-11-15 20:22:18
·
answer #5
·
answered by big T 3
·
0⤊
0⤋
3x + y = -2
y = -3x -2
Since y=mx+b, the slope is -3 and b = -2
2006-11-15 20:16:54
·
answer #6
·
answered by redstorm 3
·
0⤊
0⤋
first you need to re-arrange that equation.
rearrange it so it is....
y=-3x-2
that way, you can use the y=mx+b method to find the slope and b!
the slope... (m) is -3x
and the b is.... -2
hope this helped!
btw- i'm in algebra too! lol
2006-11-15 20:16:32
·
answer #7
·
answered by Seira T 1
·
0⤊
0⤋
move the 3x to the other side...so it becomes -3x.
therefore the slope is -3 and the b= -2
since y=mx+b
2006-11-15 20:16:28
·
answer #8
·
answered by natiassefa 2
·
1⤊
0⤋
when x is 1 what must y be ?
2006-11-15 20:16:31
·
answer #9
·
answered by pegasis 5
·
0⤊
0⤋